The impact of Polymorphisms of rs689 and rs757110 in Familial Type 2 Diabetes: A Case-Control Study in the Iranian Population - Amin Haghighi; Amaneh Javid; Ali Khodadadian; Mohammad Yahya Vahidi Mehrjardi (Iranian Journal of Diabetes and Obesity)
Objective: Understanding the genetic basis of type 2 diabetes mellitus (T2DM) is essential in getting its etiology and designing effective preventive strategies. Evaluation of the association between the gene polymorphisms rs689A/T (INS) and rs757110C/A (ABCC8) and the susceptibility to T2DM within a group of individuals diagnosed with T2DM in Iran. Materials and Methods: Blood samples were used for DNA extraction (200 with T2DM and 200 healthy controls). The quality and quantity of extracted DNA were assessed via ultraviolet spectrophotometry at 260 nm and 280 nm wavelengths. To identify specific alleles, primer sequences were manually designed using Primer3Plus, and the genotypes of rs689 (A>T) and rs757110 C>A were determined through ARMS-PCR. Statistical analysis was conducted using GraphPad Prism version 8. Results: For rs689 individuals with the genotype (AA) were found to have a higher likelihood of developing diabetes (P= 0.001). Additionally, the frequency of the A allele was found to be higher in the patient group (0.13) compared to the control group (0.05). For rs757110 individuals with the genotype (CC) were found to have a higher likelihood of developing diabetes (P< 0.001). Additionally, the frequency of the C allele was found to be higher in the patient group (0.57) compared to the control group (0.39). Conclusion: This study found that the frequency of AA and AT genotypes of rs689 and CC and CA genotypes of rs757110 are associated with T2DM risk.